Soft‐tissue tension during total hip arthroplasty measured in four patients and predicted using a musculoskeletal model - Masaru Higa; Hiromasa Tanino; Hiroshi Ito; Scott A. Banks (Journal of Experimental Orthopaedics, 2023)
Abstract Purpose Soft‐tissue tension around the hip joint is related to the incidence of dislocation after total hip arthroplasty (THA), but it remains difficult to quantify the soft‐tissue tension during surgery. In this study, a three‐dimensional force sensor‐instrumented modular femoral head was developed and used to quantify soft‐tissue tension during THA. The forces at the hip joint were also calculated using a three‐dimensional musculoskeletal computer model to validate the measured forces. Methods Soft‐tissue tension was investigated by measuring the hip joint forces and directions during intraoperative trialing in four patients through passive range of motion (ROM) from 0° extension to 90° flexion. A musculoskeletal model with THA, which was scaled to one of four patients, was developed. The hip joint forces were calculated under the same motion. Results Through the passive ROM, the magnitude of soft‐tissue tension was greatest when the hip was extended, decreased with flexion to 34°, and progressively increased to flexion at 90°. The mediolateral force component was relatively constant, but the supero‐inferior and anterior–posterior force components changed significantly. Within‐individual variations were small during three repeated cycles of measurement, but magnitudes varied significantly among patients. Similar force patterns and magnitudes were calculated by the musculoskeletal model. Conclusions This study demonstrates that it is possible to quantify soft‐tissue tension and direction during THA with an instrumented head. There was general agreement between the calculated and measured forces in both pattern and magnitude. Including additional subject‐specific details would further enhance agreement between the model and measured hip forces.